2022
DOI: 10.4103/aian.aian_1097_21
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and Mucormycosis Superinfection

Abstract: Background: Mucormycosis (MCR) has been increasingly described in patients with coronavirus disease 2019 (COVID-19), but the epidemiological factors, neurological presentation, and outcome of such patients are not well described. Aims: To study the patient demographics, presenting symptoms and signs, the role of co-morbidities, medications used to treat COVID-19, and the outcomes of management and to study the spectrum of neuraxis involvement and its outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…There have been many reports of neurological manifestations of CAM[ 1 2 ] including one in this issue of Annals of Indian Academy of Neurology. [ 5 ]…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…There have been many reports of neurological manifestations of CAM[ 1 2 ] including one in this issue of Annals of Indian Academy of Neurology. [ 5 ]…”
mentioning
confidence: 99%
“…Other known factors such as immunosuppressive therapy, underlying malignancy, chemotherapy, organ transplant, and chronic kidney disease were also seen in the studies. [ 5 10 ] Two different case-control studies have shown that use of aspirin and anti-coagulation and zinc therapy were associated with a decrease in the risk of CAM. [ 8 9 ]…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Two articles published in Jan-Feb 2022 and one in the current issue of the journal have tried to explore this mystery. [ 4 5 6 ] The estimated prevalence of mucormycosis in India is 70 times more than the global prevalence, particularly in the states of Gujarat, Maharashtra, and Karnataka. [ 7 8 9 ] Most of these cases are associated with rhinosinusitis involving the eye and/or brain (rhino-orbital/rhino-orbito-cerebral).…”
mentioning
confidence: 99%